GAMBARAN ELEKTROENSEFALOGRAFI PADA MENINGITIS TUBERKULOSIS YANG MENGALAMI BANGKITAN SIMTOMATIK AKUT - Hendra Irawan; Suryani Gunadharma; Sobaryati Sobaryati (PERDOSNI, 2020)
Introductions: Electroencephalography (EEG) can detect abnormal cortical excitability, causing epileptic seizure. Acute symptomatic seizure can caused by tuberculous meningitis (TBM) which can further develope to symptomatic epilepsy. We are interested to study the characteristic of EEG pattern in TBM patients with acute symptomatic seizure. Aims: To investigate characteristic of EEG pattern in TBM with acute symptomatic seizure. Methods: This was an descriptive observational study, from secondary medical record datas and EEG reports from acute symptomatic seizure patients caused by TBM during admited in Hasan Sadikin General Hospital, in 11 years periode from January 2006 to December 2016. Results: Fourty four subjects were enrolled in this study. The EEG pattern showed focal slowing 70.5%, 61.4% had unilateral focal slowing, and 9.1% had bilateral focal slowing. Focal epileptogenic waves were only found in 25.0% and 4.5% showed triphasic waves. Discussion: Electroencephalogram in acute symptomatic seizure due to TBM showed abnormality in 100% subjects. Almost all EEG abnormality concordances with neuro imaging findings. Keyword: Acute symptomatic seizure, EEG, tuberculous meningitis